Some clues to understand the present complex economic situation - Recio, Eugenio M. (Razón y fe, 2018)
The current world economic crisis continues to attract differing opinions. In a brief, logical and pedagogical way this short and concise article offers not only the causes of the crisis, but its consequences at global and national level. Does it remain reasonable to stay bound up to an economic system and to an economy like the one which represents the European Monetary System?